Tetramic and Tetronic Acids as Scaffolds in Bioinorganic and Bioorganic Chemistry - G. Athanasellis; O. Igglessi-Markopoulou; J. Markopoulos (Bioinorganic Chemistry and Applications)
Tetramic and tetronic acids are naturally occurring molecules with a variety of biological activities. In this review article, we present the general strategies for the synthesis of these compounds and we reveal the functionalized groups that are responsible for their properties. We also set out their coordinating modes with up-to-date bibliographical references.